2013
DOI: 10.1007/s13277-013-0959-9
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in apoptosis and cell cycle by celecoxib and/or fish oil in 7,12-dimethyl benzene (α) anthracene-induced mammary carcinogenesis

Abstract: Cyclooxygenase (COX)-2 inhibition by nonsteroidal anti-inflammatory drugs is a useful approach for cancer prevention but has several side effects. A novel approach combining these chemopreventive agents at low doses with dietary elements has been suggested to augment their effects and reduce side effects. Dietary fats, particularly, n-3 polyunsaturated fatty acids (PUFA) also exert cancer chemopreventive effect mediated through COX-2 inhibition. Therefore, the present study was designed to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Other important experimental conditions include when in an animal’s lifespan supplementation is started (younger may be more protective than older), and whether agent is added to feed or administered by gavage as omega-3 fatty acids are readily oxidized once exposed to light [ 38 ]. Several preclinical studies suggest that EPA/DHA supplementation may be most optimal for prevention of estrogen receptor-positive breast cancer when used with another chemoprevention agent such as vitamin D [ 41 ], a selective estrogen receptor modulator [ 43 ], or celecoxib [ 42 ].…”
Section: Preclinical Models Of Mammary Cancer Preventionmentioning
confidence: 99%
“…Other important experimental conditions include when in an animal’s lifespan supplementation is started (younger may be more protective than older), and whether agent is added to feed or administered by gavage as omega-3 fatty acids are readily oxidized once exposed to light [ 38 ]. Several preclinical studies suggest that EPA/DHA supplementation may be most optimal for prevention of estrogen receptor-positive breast cancer when used with another chemoprevention agent such as vitamin D [ 41 ], a selective estrogen receptor modulator [ 43 ], or celecoxib [ 42 ].…”
Section: Preclinical Models Of Mammary Cancer Preventionmentioning
confidence: 99%
“…Mice treated with 20 mg/ml/week DMBA only to induce breast cancer (the dose as described by Minari and Okeke (2014) [7,8].…”
Section: Group IImentioning
confidence: 99%
“…Furthermore, we have recently shown that the tumor microenvironment was associated with substantial features of inflammatory marker including hypoxia and oncogenic activities (Omabe and Onyekachi, 2013) (figure 1). Another preclinical study that involved combining dosage of celecoxib (a known cox-2 inhibitor) and a dietary fats, n-3 polyunsaturated fatty acids (PUFA) often found in fish oil (which exerts cancer chemo preventive effect mediated through COX-2 inhibition); revealed that pretreatment of carcinogen-treated animals with celecoxib and/or fish oil altered inflammation mediated redox signaling with reduced c-myc, p53 expression, apoptosis, and proliferation in breast cancer model (Negi et al, 2013). However, a combination dosage of celecoxib and fish oil treatment in that study resulted in better chemo preventive effect in the female Wistar rats (Negi et al, 2013).…”
Section: Targeting Inflammatory Markers For Cancer Treatments and Prementioning
confidence: 99%
“…Another preclinical study that involved combining dosage of celecoxib (a known cox-2 inhibitor) and a dietary fats, n-3 polyunsaturated fatty acids (PUFA) often found in fish oil (which exerts cancer chemo preventive effect mediated through COX-2 inhibition); revealed that pretreatment of carcinogen-treated animals with celecoxib and/or fish oil altered inflammation mediated redox signaling with reduced c-myc, p53 expression, apoptosis, and proliferation in breast cancer model (Negi et al, 2013). However, a combination dosage of celecoxib and fish oil treatment in that study resulted in better chemo preventive effect in the female Wistar rats (Negi et al, 2013). The results suggest that a combination of celecoxib and fish oil which provide better anti-inflammatory synergy would be more effective in the chemoprevention of experimental mammary carcinogenesis, and this effect can be attributed to the modification of redox signaling.…”
Section: Targeting Inflammatory Markers For Cancer Treatments and Prementioning
confidence: 99%